(untitled) (Reflection and Critique Law Magazine, 2025)
This article examines the intersection between Advance Directives (AD) and religious freedom, focusing specifically on the refusal of medical treatment by Jehovah’s Witnesses. The study explores the legal and ethical foundations supporting the use of ADs by members of this religious group, considering the lack of specific regulations in Brazilian law and the fundamental right to religious freedom. The research begins with a constitutional analysis, exploring the tension between the right to life, religious freedom, and patient autonomy. It employs the principle of balancing, as proposed by Luiz Roberto Barroso, as a methodology to address the conflict between these fundamental rights. The article also examines recent Supreme Federal Court jurisprudence, which has favored patient autonomy in similar cases.The social function of contracts and its applicability to ADs are discussed, considering them as an expression of individual autonomy. Crucial ethical issues are addressed, such as the legitimacy of the state in imposing medical treatments contrary to the patient’s conscience and faith, and the dilemmas faced by healthcare professionals in these situations.The study concludes that the will expressed in ADs should be respected, provided they are prepared by a capable person free from consent defects. It argues that such respect is based on both the legal validity of the public document and the constitutional guarantee of religious freedom. Finally, the article proposes the urgency of specific regulations for ADs in Brazil, considering international experiences and the peculiarities of the Brazilian legal and cultural context. Such regulation would aim to provide greater legal certainty for patients, healthcare professionals, and medical institutions, especially in cases involving religious convictions such as those of Jehovah’s Witnesses.